Optimization of nutrient solution management for leafy greens production in recirculating hydroponic systems under controlled environments - Subedi, Puja (My University, 2025)
Nutrient solution (NS) and electrical conductivity (EC) management of soilless cropping systems is crucial to optimize the yield and quality of hydroponic crops. The first objective of this thesis was to complete a comprehensive review of current nutrient management strategies in recirculating hydroponic systems, including hydroponic systems design, nutrient formulations, and nutrient management strategies. The review identified critical gaps in knowledge relating to how NS volume in recirculating hydroponic systems impacts nutrient management, along with gaps in knowledge to optimize EC for less-studied leafy greens, such as kale (Brassica oleracea ‘Winterbor F1’) and Malabar spinach (Basella alba ‘Rubra’), which may have different nutrient requirements compared to lettuce (Lactuca sativa ‘Salanova Red Butter’) and basil (Ocimum basilicum ‘Large leaf’), which are most frequently studied. Secondly, two greenhouse experiments were conducted to study the effect of NS volume low (75 L; 2 L per plant) or high (150 L; 4 L per plant) on growth, yield, tissue nutrient concentration; and postharvest quality parameters, including vitamin C, anthocyanins, total phenolics, and antioxidant capacity of four leafy greens species: butterhead lettuce (Lactuca sativa ‘Salanova Red Butter’), arugula (Eruca sativa ‘Standard’), kale (Brassica oleracea ‘Red Russian’), and the emerging crop Malabar spinach (Basella alba ‘Rubra’). Results showed that using a low NS volume resulted in higher nitrogen (N) uptake efficiency and lower N retention in the nutrient film technique (NFT) system in both seasons’ trials. NS volume had no impact on growth and yield parameters, but it influenced nutrient composition and quality attributes of leafy greens. Tissue N and potassium (K) in summer and phosphorus (P) and K in fall increased with high volume. Low NS volume reduced nitrate levels in shoots of arugula, lettuce, and Malabar spinach during both seasons, suggesting that lower volume may help minimize excessive nitrate levels in plant shoots, while kale consistently surpassed recommended safe nitrate levels regardless of treatment. NS volume influenced key postharvest attributes of color, total phenolics, and antioxidant capacity. Third, in experiments with indoor growth tents, effects of NS EC levels (standard:1.8 and elevated: 3.6 mS.cm⁻¹) on growth, yield, shoot nutrient concentrations, and postharvest nutritional quality of four leafy green species (basil, kale, lettuce and Malabar spinach) were studied. Plant height and SPAD values were higher with elevated EC across species, with SPAD particularly increased in Malabar spinach. Shoot fresh weight was increased by elevated EC across all species. Shoot and root dry weights were increased by elevated EC, particularly in kale. Tissue analyses revealed high potassium (K) concentration at elevated EC. Standard EC reduced nitrate levels in basil, lettuce, and Malabar spinach within safe range limits, while kale surpassed recommended safe nitrate levels regardless of treatment. Standard EC levels could be a potential strategy to produce K-limited leafy greens to support a low K diet for kidney-diseased patients. Postharvest quality, including color, texture, and nutritional quality, vitamin C, anthocyanin, total phenolics, and antioxidant capacity, was not affected by EC levels. Based on our results, standard EC is optimal for basil and lettuce, while elevated EC may benefit kale and Malabar spinach. For Malabar spinach, high wire production systems should be explored to support its vining growth habit and extend harvest duration to increase yield. This thesis advances the understanding of species-specific responses to nutrient solution volume and EC in recirculating hydroponic systems, providing evidence-based recommendations to improve nutrient use efficiency, crop nutritional quality, and sustainability in controlled environment agriculture.
Keywords: Nutrient budget; Malabar spinach; Nutrient film technique; Vertical hydroponic system; Antioxidants; Phenolics